2014
DOI: 10.14432/j.macvetrev.2014.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Glutathione on Kinetic Parameters of Frozen-Thawed Spermatozoa from Ovchepolian Pramenka Rams

Abstract: Motility patterns of spermatozoa are an indicator of their fertilizing capacity. Reduced glutathione (GSH) has been reported to induce positive effects on the biological quality of the frozen-thawed spermatozoa. The aim of this study was to investigate the effects of GSH addition to semen extender based on the following kinetic parameters: continuous line velocity (VSL), average path velocity (VAP), curvilinear velocity (VCL), amplitude of lateral head displacement (ALH), linearity (LIN), straightness (STR), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…CASA methods allow the possibility of real-time analysis of spermatozoon kinetic parameters, providing fast and accurate results. They have good predictive value for fertilization ability (Nikolovski et al, 2014). Robayo et al (2008) reported that the progression of spermatozoa in sheep cervical mucus was positively correlated with the kinetic parameter VCL.…”
Section: Discussionmentioning
confidence: 99%
“…CASA methods allow the possibility of real-time analysis of spermatozoon kinetic parameters, providing fast and accurate results. They have good predictive value for fertilization ability (Nikolovski et al, 2014). Robayo et al (2008) reported that the progression of spermatozoa in sheep cervical mucus was positively correlated with the kinetic parameter VCL.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous researchers have been focusing on the effects of different antioxidants supplemented to sperm cryopreserving media (oxidized glutathione-GSSG, reduced glutathione-GSH, cysteine) in aim to reduce the vii oxidative stress when supplemented in ram semenfreezing media. Most of these studies reported that these antioxidants have no effect in increasing ram sperm viability during cryopreservation (40,41).…”
Section: Semen Conservation/preservationmentioning
confidence: 99%
“…Using antioxidants as a protective agent against the formation of free radicals is known scientifically as a strong tool in decreasing oxidative stress and maintaining the biological activities of cells. The use of antioxidants has a confirmed positive action on enhancing the fertile properties of semen because they scavenge free radicals that form during the metabolic activities of sperm and leukocytes, they decrease the development of premature sperm, and they prevent DNA fragmentation of sperm (Nikolovski et al 2014).…”
Section: Introductionmentioning
confidence: 99%